Negotiating Gender Identity and Power: A Sociolinguistic Analysis of Women's Language in Divergent Movie - Ligatu, Bulan Hontinimbang; Bouti , Suleman; Malabar , Fahria (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study examines how Lakoff’s women’s language features appear in the speech of Beatrice Prior in the film Divergent (2014). The research focuses on three aspects: the types of women’s language feature she uses, how these features are distributed across Abnegation and Dauntless, and how Beatrice’s social roles influence her linguistic choices. This study uses a descriptive qualitative approach, and the data consist of selected utterances that are classified based on Lakoff’s framework. The findings show that Beatrice uses several features such as lexical hedges, intensifiers, super polite forms, tag questions, and rising intonation. These features appear differently depending on the setting. In Abnegation, her speech is more polite and controlled, reflecting the values of the faction. After joining Dauntless, her language becomes more expressive and direct. The analysis also indicates that her shifts in social roles contribute to the changes in the way she speaks. The study highlights that her linguistic style adapts to the environment and the roles she performs throughout the story.